1998
DOI: 10.1152/ajpcell.1998.274.5.c1253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phorbol esters on Ca2+ sensitivity and myosin light-chain phosphorylation in airway smooth muscle

Abstract: We studied in β-escin-permeabilized canine tracheal smooth muscle (CTSM) the effect of the protein kinase C (PKC) agonist phorbol 12,13-dibutyrate (PDBu) on isometric force at a constant submaximal Ca2+ concentration (i.e., the effect on Ca2+ sensitivity) and regulatory myosin light-chain (rMLC) phosphorylation. PDBu increased Ca2+sensitivity, an increase associated with a concentration-dependent, sustained increase in rMLC phosphorylation. PDBu altered the relationship between rMLC phosphorylation and isometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…This relaxing effect of caffeine was also observed in model or normal airways in the absence of MCh. -induced airway contraction in the presence of GPCR agonist such as ACh, carbachol and endothelin-1 has also been previously observed in permeabilized tracheal SMCs from pig, dog, rabbit, rat, and mouse as well as surgically resected human bronchial SMCs (6,7,10,23,25,32). However, this vital role of GPCR agonists in establishing the sensitivity to Ca 2ϩ for the maintenance of intrapulmonary airway contraction was not previously recognized.…”
Section: Discussionmentioning
confidence: 90%
“…This relaxing effect of caffeine was also observed in model or normal airways in the absence of MCh. -induced airway contraction in the presence of GPCR agonist such as ACh, carbachol and endothelin-1 has also been previously observed in permeabilized tracheal SMCs from pig, dog, rabbit, rat, and mouse as well as surgically resected human bronchial SMCs (6,7,10,23,25,32). However, this vital role of GPCR agonists in establishing the sensitivity to Ca 2ϩ for the maintenance of intrapulmonary airway contraction was not previously recognized.…”
Section: Discussionmentioning
confidence: 90%
“…Chelerythrine inhibited protein kinase C activity by interacting with the catalytic domain of the enzyme, whereas it did not inhibit activity of tyrosine protein kinase, calcium/ calmodulin-dependent protein kinase or cyclic AMP-dependent kinase (Herbert et al, 1990). Chelerythrine inhibited PDBu-induced Ca 2 þ sensitization in canine tracheal smooth muscle (Bremerich et al, 1998) and porcine pulmonary artery (Kutz et al, 1998). In the present study, both PKC(19-31) and chelerythrine significantly inhibited PDBu-induced Ca 2 þ sensitization, but not GTP-induced Ca 2 þ sensitization in preparations of both regions of the colon, indicating the specificity of these compounds to protein kinase C. Thus, these T. Takeuchi et al Ca 2 þ sensitization in rat colon 663 results suggested that CCh-induced Ca 2 þ sensitization was solely through the rho pathway in the rat proximal colon.…”
Section: T Takeuchi Et Almentioning
confidence: 89%
“…Recent studies by Bremerich et al (1998) have con®rmed that PDBu increases LC 20 phosphorylation in b-escinpermeabilized canine trachealis at a constant Ca 2+ concentration. However, these investigators provided two pieces of evidence against the idea that LC 20 phosphorylation accounts for force development under these conditions.…”
Section: Force Maintenancementioning
confidence: 99%
“…Recent studies by Bremerich et al . (1998) have confirmed that PDBu increases LC 20 phosphorylation in β‐escin‐permeabilized canine trachealis at a constant Ca 2+ concentration.…”
Section: Pkc and Contractionmentioning
confidence: 99%
See 1 more Smart Citation